2017
DOI: 10.1016/j.stemcr.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

HuCNS-SC Human NSCs Fail to Differentiate, Form Ectopic Clusters, and Provide No Cognitive Benefits in a Transgenic Model of Alzheimer's Disease

Abstract: SummaryTransplantation of neural stem cells (NSCs) can improve cognition in animal models of Alzheimer's disease (AD). However, AD is a protracted disorder, and prior studies have examined only short-term effects. We therefore used an immune-deficient model of AD (Rag-5xfAD mice) to examine long-term transplantation of human NSCs (StemCells Inc.; HuCNS-SCs). Five months after transplantation, HuCNS-SCs had engrafted and migrated throughout the hippocampus and exhibited no differences in survival or migration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 45 publications
1
60
0
Order By: Relevance
“…However, very recent clinical trial data highlight critical issues with tissue‐source cells. Using tissue‐source neural stem cells (NSCs), two recent clinical trials reported surprisingly negative results despite previous animal studies demonstrating therapeutic efficacy . Reasons that could account for these unexpected disappointing results with regard to the cellular produce itself include inherent donor‐specific genetic differences and NSC heterogeneity, as well as extrinsic factors during the manufacturing process, which can all add to inconsistencies in the end product .…”
Section: Discussionmentioning
confidence: 99%
“…However, very recent clinical trial data highlight critical issues with tissue‐source cells. Using tissue‐source neural stem cells (NSCs), two recent clinical trials reported surprisingly negative results despite previous animal studies demonstrating therapeutic efficacy . Reasons that could account for these unexpected disappointing results with regard to the cellular produce itself include inherent donor‐specific genetic differences and NSC heterogeneity, as well as extrinsic factors during the manufacturing process, which can all add to inconsistencies in the end product .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is becoming increasingly clear that no two NSC lines are completely equivalent. Even when derived from similar source material using similar methods we have found disparate differences in NSC phenotype and behavior (Ager et al, 2015, Marsh et al, in press). It follows that identifying the optimal NSC line for clinical translation may be extremely challenging and that clinical grade NSC lines intended for trials need to be individually tested for efficacy and safety in appropriate animal models prior to translation.…”
Section: Remaining Challengesmentioning
confidence: 81%
“…The establishment of a xeno-free system is increasingly important for preclinical investigations, as recent studies have reported the failure of clinical-grade NSCs in pre-clinical models of SCI (Anderson, Piltti, Hooshmand, Nishi, & Cummings, 2017) and Alzheimer's disease (Marsh et al, 2017), despite the efficacy of research-grade cells. To our best knowledge, this study is the first to report the successful derivation of forebrain OPCs from hPSCs under a xeno-free condition.…”
Section: Discussionmentioning
confidence: 99%